2005
DOI: 10.1024/0301-1526.34.3.186
|View full text |Cite
|
Sign up to set email alerts
|

Transluminal angioplasty of isolated crural arterial lesions in diabetics with critical limb ischemia

Abstract: Our results suggest that depending on the extent of lesions transluminal angioplasty of infrapopliteal artery stenoses and occlusions is considered as an effective and save therapy modality to avoid limb loss in diabetics with critical ischemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
1
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 0 publications
0
29
1
1
Order By: Relevance
“…2 Other studies have shown that if only the superficial femoral artery (SFA) needs to be revascularized, there are better limb salvage rates and that failure of limb salvage is much more likely to occur in Trans-Atlantic Inter-Society Consensus (TASC) C and D lesions. [3][4][5] Our group has previously presented data which demonstrated that isolated infrapopliteal subintimal percutaneous transluminal angioplasty (PTA) had poor utility in healing forefoot wounds despite technical success. 6 Another group has shown that a Rutherford (Society of Vascular Surgery [SVS]) ischemia grade of 5 or greater is independently associated with percutaneous intervention failure.…”
Section: Introductionmentioning
confidence: 98%
“…2 Other studies have shown that if only the superficial femoral artery (SFA) needs to be revascularized, there are better limb salvage rates and that failure of limb salvage is much more likely to occur in Trans-Atlantic Inter-Society Consensus (TASC) C and D lesions. [3][4][5] Our group has previously presented data which demonstrated that isolated infrapopliteal subintimal percutaneous transluminal angioplasty (PTA) had poor utility in healing forefoot wounds despite technical success. 6 Another group has shown that a Rutherford (Society of Vascular Surgery [SVS]) ischemia grade of 5 or greater is independently associated with percutaneous intervention failure.…”
Section: Introductionmentioning
confidence: 98%
“…7 Although numerous previously published studies involving diabetic patients demonstrated that infrapopliteal intervention in this group may salvage the majority of limbs under threat of amputation, these studies dealt with heterogeneous stages of ischemia such as claudication, resting pain or tissue lesions and, furthermore, the most frequently treated vessels were the distal popliteal artery and the tibioperoneal trunk, whose diameters are more similar to those of above-knee arteries than those of the smaller below-knee arteries. 8- 15 A recent study reported that a successful endovascular procedure led to a high percentage of limb salvage at long-term follow-up in the patients with ischemic diabetic foot and isolated below-knee lesions. 16 In the present study, we compared the outcomes of infrapopliteal angioplasty between Korean diabetic patients and non-diabetic patients with CLI.…”
mentioning
confidence: 99%
“…PTA has established itself as a first-line treatment for CLI in patients with diabetic foot, with similar results to surgery in terms of limb salvage and patency [8][9][10]. The main studies in the literature [13,16,[23][24][25][26][27][28][29][30] reported, for endovascular treatment, a technical success rate of about 90 %, a negligible mortality rate, and a limb salvage rate at 3-5 years of 72-98 %.…”
Section: Discussionmentioning
confidence: 99%
“…The primary goal of PTA treatment is to restore the patency of at least one below-the-knee (BTK) vessel, preferably the tributary of the anatomical region of the ulcer [9]. Several studies have demonstrated good results in terms of patency and limb salvage after endovascular treatment of diabetic foot [10][11][12][13][14]. Many, however, are limited by the presence of a heterogeneous population with different stages of ischemia (claudication, rest pain, trophic lesions) and different treatment modalities, with PTA performed both in the above-the-knee (ATK) and BTK areas [15][16][17].…”
Section: Introductionmentioning
confidence: 99%